The Position of Negative Element in Prepositional Phrases with Negative Indefinites - Zovko Dinković, Irena (2014)
Croatian negative indefinite expressions, or the so-called ni-words, are complex forms made by adding the prefix ni- to simple forms of indefinite pronouns tko 'who', što/šta 'what', čiji 'whose', kakav 'what kind (of)', koji 'which', the adverb malo 'a little', interrogative adverbs kad(a) 'when', gdje 'where', kamo 'where to', kud(a) 'where by', otkud(a) 'where from' and the number jedan 'one'. The Croatian standard norm prescribes that in prepositional phrases involving negative idefinite pronouns (s.c. ni-pronouns) the negative element ni should be separated from the pronoun and put in front of the preposition. However, in everyday communication one may often notice the use of the word order P + negative indefinite pronoun, and this word order has also made its way into newspapers and other media. This paper attempts to determine whether there is a significant difference in meaning between the order ni + P + indefinite pronoun and the order P + negative indefinite pronoun to account for such a change in language. We also analyze the frequency of use of these two different word orders in the Croatian National Corpus, examining eleven most frequent prepositions and five indefinite pronouns.
Projekt MZOS
ENG